Analisis Faktor Lingkungan dan Akses Pelayanan Kesehatan Dengan Kejadian Malaria di Daerah Rawan Malaria di Wilayah Kerja Puskesmas Penimbung Kecamatan Gunungsari Kabupaten Lombok Barat - Desimal, Iwan; Ningsih, Murtiana; Zaida, Una; Ariany, Farida (LPPM Institut Pendidikan Nusantara Global, 2024)
West Lombok Regency, especially Gunungsari District, namely the Penimbung Health Center, had an outbreak (Extraordinary Events / KLB) in 2018. The distribution of positive malaria based on data from the Penimbung Health Center, namely in 2018, there were 753 positive confirmed cases. This incident was the first time an outbreak had occurred and was a tough homework for the Penimbung Health Center. The increase in malaria cases is closely related to environmental factors as an ecological disease. Not only environmental factors, the factor of access to health services is very influential on the threat of the final outcome in the implementation of development in the health sector, especially malaria elimination. This type of research is analytic observational, the research design uses cross sectional. The number of samples is 84 (cases and controls). Data were analyzed using multiple logistic regression analysis (α = 5%). The results of the study showed that there was a relationship altitude, distance and travel time to health services with the incidence of malaria (p value <5%).